HUBUNGAN ANTARA KREATIVITAS DALAM MENGOLAH SUMBER DAYA PERIKANAN LAUT DENGAN PEMENUHAN KEBUTUHAN DASAR PEREMPUAN PESISIR DI DESA BUNGKO LOR KABUPATEN CIREBON, JAWA BARAT - Friska Febriani; Yuce Sariningsih (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
Creativity is the potential of all people who do not need special talents and abilities, generally people actually lose creativity because of the cultivation process including formal education that promotes creativity and provides a gap in society that only educated people can be seen, listened to and respected, this is the same thing that makes coastal communities rarely seen. And the processing of marine fishery resources is a form of embodiment of creativity, this research was raised with the title